Engagement in entrepreneurship in emerging economies: Interactive effects of individual-level factors and institutional conditions. Issue 4 (August 2016) - Lim, Dominic S.K.; Oh, Chang Hoon; De Clercq, Dirk
Abstract: This paper examines individuals' engagement in entrepreneurship in emerging economies. We conceive of such engagement as encompassing opportunity discovery, evaluation, and exploitation. We investigate the influence of individuals' household income and level of education on their engagement in entrepreneurship, as well as the interaction effects between these individual-level factors and country-level regulatory, cognitive, and normative institutions. We test our hypotheses on a multi-source dataset from 22 emerging economies using a multilevel analysis technique. Our results indicate that the direct effect of individuals' household income on their engagement in entrepreneurship is persistent, regardless of institutional conditions; but the influence of education level varies contingent upon various institutional conditions.